PROBLEMS OF MODERN PRE-HOSPITAL CARE AND DISASTER MEDICINE (Herald of the National Children's Medical Center, 2022)
This article is devoted to terminological problems that occur while providing medical care to injured persons at theplace where an incident had happened by people with no medical education. First aid is a set of urgent measures aimed atsaving the life and health of a person in a critical situation, and is provided by persons who are directly nearby. First aid isnot medical - it is provided before the arrival of medics or the delivery of the victim to the hospital. It can be provided byanyone, but for some categories of citizens, Brst aid is an ofBcial duty. They may not be able to quickly meet your specialneeds as they tend to reach out to those who are seriously injured or trapped.
Keywords: natural disasters; earthquake; Eood; injured; Brst aid; timely; rescuers; medical workers